Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/0020294020935492
|View full text |Cite
|
Sign up to set email alerts
|

On disturbance rejection control for inertial stabilization of long-distance laser positioning with movable platform

Abstract: This paper focuses on the disturbance rejection control problem for inertial stabilization of long-distance laser positioning with the movable platform. Due to various disturbances of the movable platform, the positioning system has significant disturbances that affect the positioning accuracy. Moreover, the nonminimum-phase property of the inertial stabilization system leads to great challenges for designing traditional disturbance-observer-based as well as rejection control methods. In this paper, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
5
0
4
Order By: Relevance
“…Next, the performance difference between the SMC based on the DOB and the SMC based on IMC was verified by comparative simulation. To show the superiority of the proposed algorithm, three different DOBs were designed and are presented in this subsection; they were: the conventional DOB (CDOB) [43], the dual-compensator DOB (DCDOB) [44] and the novel sliding mode DOB (NSMDOB) [7]. To ensure the relative fairness of the comparison, the SMC with the same parameters was invoked as the closed-loop controller.…”
Section: Simulation Analysismentioning
confidence: 99%
“…Next, the performance difference between the SMC based on the DOB and the SMC based on IMC was verified by comparative simulation. To show the superiority of the proposed algorithm, three different DOBs were designed and are presented in this subsection; they were: the conventional DOB (CDOB) [43], the dual-compensator DOB (DCDOB) [44] and the novel sliding mode DOB (NSMDOB) [7]. To ensure the relative fairness of the comparison, the SMC with the same parameters was invoked as the closed-loop controller.…”
Section: Simulation Analysismentioning
confidence: 99%
“…Los sistemas de control para el posicionamiento y estabilización de haz láser LBS (por sus siglas en inglés, Laser Beam Stabilization) son usados en diferentes sistemas tecnológicos en donde una gran precisión y robustez es requerida. Algunos ejemplos de estas aplicaciones son los cortadores láser en diferentes sistemas de manufactura, la cirugía robótica, comunicaciones ópticas, aplicaciones de astronomía, el escaneo de códigos de barras, entre otros (Quanser, 2010;Martinez et al, 2009;Alizadegan et al, 2018;Deng et al, 2020). Las técnicas de control para el posicionamiento del haz láser son la clave en muchos de los sistemas de óptica adaptable.…”
Section: Introductionunclassified
“…El problema de control para el posicionamiento y direccionamiento del haz láser, consiste en lograr la regulación de la posición del haz o el seguimiento de una trayectoria, lo cual es establecido por el usuario. Sin embargo, la exactitud del posicionamiento del haz láser es afectado por perturbaciones externas, con componentes de media y baja frecuencia, provocadas principalmente por el movimiento o las vibraciones presentes en la plataforma donde se instala (Kim et al, 2004;Deng et al, 2020). En los sistemas optomecatrónicos, como el utilizado en la presente investigación, se utiliza un espejo activo con el objetivo de lograr el rechazo a las perturbaciones y posicionar de manera precisa el haz láser en la posición deseada, ver Figura 1.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…1.1 Introduction: robust control of uncertain systems Furthermore, if the search is focused on specic application areas, it is found that robust controllers specically DOBCs, ADRCs and sliding mode controllers are being applied in: motion control (Umeno et al 1991;Choi et al 1999;Sariyildiz et al 2015), power electronics (Yokoyama et al 1994;Jain et al 2020), fault diagnosis (Wang et al 1996;Han et al 2018;Bernardi et al 2020), automobiles (Bünte et al 2002;Kadowaki et al 2002;Fujimoto et al 2004), underwater vehicles (Peng et al 2017), networks (Natori et al 2008), missile seekers (Sadhu et al 2010), spacecrafts (Liu et al 2018), UAVs (Castillo et al 2019a), surgery/rehabilitation robots (Ugurlu et al 2014), long-distance laser positioning (Deng et al 2020) and magnetic levitation (Yang et al 2011); among many others.…”
Section: Prefacimentioning
confidence: 99%